Role of Mitogen-Activated Protein Kinases in Myocardial Ischemia-Reperfusion Injury during Heart Transplantation - Giuseppe Vassalli; Giuseppina Milano; Tiziano Moccetti (Journal of Transplantation)
In solid organ transplantation, ischemia/reperfusion (IR) injury during organ procurement, storage and reperfusion is an unavoidable detrimental event for the graft, as it amplifies graft inflammation and rejection. Intracellular mitogen-activated protein kinase (MAPK) signaling pathways regulate inflammation and cell survival during IR injury. The four best-characterized MAPK subfamilies are the c-Jun NH2-terminal kinase (JNK), extracellular signal- regulated kinase-1/2 (ERK1/2), p38 MAPK, and big MAPK-1 (BMK1/ERK5). Here, we review the role of MAPK activation during myocardial IR injury as it occurs during heart transplantation. Most of our current knowledge regarding MAPK activation and cardioprotection comes from studies of preconditioning and postconditioning in nontransplanted hearts. JNK and p38 MAPK activation contributes to myocardial IR injury after prolonged hypothermic storage. p38 MAPK inhibition improves cardiac function after cold storage, rewarming and reperfusion. Small-molecule p38 MAPK inhibitors have been tested clinically in patients with chronic inflammatory diseases, but not in transplanted patients, so far. Organ transplantation offers the opportunity of starting a preconditioning treatment before organ procurement or during cold storage, thus modulating early events in IR injury. Future studies will need to evaluate combined strategies including p38 MAPK and/or JNK inhibition, ERK1/2 activation, pre- or postconditioning protocols, new storage solutions, and gentle reperfusion.